2011
DOI: 10.12659/msm.881922
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood transfusion in the treatment of an acute organophosphorus poisoning – a case report

Abstract: SummaryBackgroundOrganophosphorus compounds (OP) are a group of substances used in agriculture as pesticides and are also used as military poisoning agents (MPA). Intoxication by these agents may cause severe systemic disturbances related to both the exposure time and lethal agent concentration. Toxic effects result from an excess of the endogenous neurotransmitter, acetylcholine (ACh), because decomposition of Ach by cholinesterases is blocked by OP.Case ReportThe authors describe a case in which an acute OP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Research has shown that the major mechanism of organophosphorus pesticide poisoning is the inhibition of organic phosphorus acting on cholinesterase. This inhibition leads to a large accumulation of acetylcholine in the tissue space, which further results in a series of dysfunctions in the nervous system, myocardial cells, and respiration (3,4). Severe AOPP can cause acute cholinergic crisis, including the stimulation of nicotinic receptors and muscarinic receptors, which leads to the main cause of death, namely respiration failure (5).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the major mechanism of organophosphorus pesticide poisoning is the inhibition of organic phosphorus acting on cholinesterase. This inhibition leads to a large accumulation of acetylcholine in the tissue space, which further results in a series of dysfunctions in the nervous system, myocardial cells, and respiration (3,4). Severe AOPP can cause acute cholinergic crisis, including the stimulation of nicotinic receptors and muscarinic receptors, which leads to the main cause of death, namely respiration failure (5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported whole blood transfusion [9] or fresh frozen plasma transfusion [14] could restore the enzymatic function by its biscavenging effect. However, packed RBCs transfusion has advantages over whole blood transfusion, since the total volume administrated into patients is less that could avoid risks of overloading and fever or allergy by substances in serum.…”
Section: Discussionmentioning
confidence: 99%
“…OP intoxications are potentially fatal poisonings which result from both accidental and purposeful intake. These poisoning could be acute or chronic, with high risk of remote consequences [9]. OP compounds are very strong inhibitors for carboxylic ester hydrolases.…”
Section: Discussionmentioning
confidence: 99%
“…OPs like DZN exert their detrimental effects through oxidative stress, oxidation of lipids, proteins and DNA in the testis [43]. Ahmed and et al reported that administration of ginger with biological activities improves sperm parameters [32].…”
Section: Discussionmentioning
confidence: 99%